The Impact Of Clinical Nurses’ Perception Of Hospital Ethical Climates On Their Organizational Citizenship Behavior - Alansari, Mohsenah Thaar; Alhazmi, Ameen Mosa F; Al-Zahrani, Fahad Khadhran Saleh; Alzahrani, Saeed Mansour; Alzahrani, Jamaan Ahmed Abudullah; Hawthan, Abdu Qasem; Al-Moqati, Bander Mohammed Obaid; Ali Salama Ibrahim Alhazmi; Marayam Rabah Hamad Almoseiry; Rehab Hemidan Hamed Alloqmani (Migration Letters, 2023)
Background: As the main force in the development of healthcare, nurses have the longest contact time with patients in clinical practice, their perception of the hospital ethical climates affecting nurses’ attitudes and related ethical issues. Hospital ethical climates have become an essential environmental factor for nurses to make and implement ethical decisions. This study aims to investigate the current status of nurses’ perception of the hospital ethical climates and the nurses’ organizational citizenship behavior, exploring the impact of the nurse’s perception of the hospital ethical climates on the nurses’ organizational citizenship behavior. Methods: A cross-sectional survey adopted, random sampling and cluster sampling were used to select 624 nurses from February to May 2023 at KSA. The hospital ethical climate scale and organizational citizenship behavior scale were used as the questionnaire. The data was analyzed by SPSS 28.0 software. On-the-job clinical nurses who had been employed in the hospital for more than 1 year were eligible. Nurses who were administratively punished by the hospital or health administrative authorities were excluded. Results: The average scores of hospital ethical climates were 4.30 (SD 0.44), with organizational citizenship behavior 4.42 (SD 0.42). The correlation coefﬁcient between nurses’ perception of hospital ethical climates and organizational citizenship behavior was 0.359 (P < .01). Nurses’ perception of the relationship between managers, patients and nurses could explain 23.1% of altruistic toward colleagues; Nurses’ perception of the relationship between nurses, hospital, doctors could explain 21.2% of organizational identiﬁcation. Nurses’ perception of the relationship between hospital, nurses and doctors could explain 12.3% of conscientiousness; Nurses’ perception of the relationship between managers, doctors could explain 7.6% of interpersonal harmony. Nurses’ perception of the relationship between managers, nurses and doctors could explain 6.6% of protection company resources. Conclusion: There is a correlation between nurses’ perceptions of hospital ethical climate and organizational citizenship behavior, nurses’ perceptions of hospital ethical climate inﬂuencing nurses’ organizational citizenship behavior in different ways. Managers should focus on the changes of nurses’ perception of hospital ethical climates.